Serratia marcescens Strain VIRS2 Isolated from Saline Soil Enhances Rice Growth and Salt Tolerance - Tuong M. Ho; Manh V. Le; Ha H. T. Nguyen; Quyen Phan; Thao P. Bui; Linh K. Ly; Van B. Lam; Michiel Vandecasteele; Sofie Goormachtig; Ha H. Chu; Phat T. Do (Microbiology Research)
Soil salinization, a major challenge caused by climate change over the past century, critically affects cultivated land and consequently reduces agricultural production worldwide. Recently, plant growth-promoting rhizobacteria have been collected and utilized to enhance plant growth and mitigate the effects of salt stress in different plant species including rice. In our current study, the Serratia marcescens strain VIRS2 with remarkable salt tolerance was successfully isolated from the saline soil in the Mekong River Delta of Vietnam. This isolate exhibited diverse plant growth-promoting properties, especially the production of a high indole acetic acid level. Treatments under both in vitro and greenhouse conditions indicated that VIRS2 could enhance growth and salt tolerance in rice. The VIRS2-inoculated rice plants exhibited biochemical profile alterations including proline, malondialdehyde, and relative water contents. In addition, the expression of genes involved in the plant stress response pathways was upregulated in the VIRS2-inoculated rice under salt treatments. Importantly, the whole genome sequencing data of VIRS2 also showed the presence of different genes associated with plant growth-promotion and stress-tolerance mechanisms. These results indicated the potential of the VIRS2 isolate for enhancing growth and salt tolerance in rice as well as other important crops.